2011
DOI: 10.2337/dc10-1675
|View full text |Cite
|
Sign up to set email alerts
|

Protection From Retinopathy and Other Complications in Patients With Type 1 Diabetes of Extreme Duration

Abstract: OBJECTIVETo assess complication prevalence and identify protective factors in patients with diabetes duration of ≥50 years. Characterization of a complication-free subgroup in this cohort would suggest that some individuals are protected from diabetes complications and allow identification of endogenous protective factors.RESEARCH DESIGN AND METHODSCross-sectional, observational study of 351 U.S. residents who have survived with type 1 diabetes for ≥50 years (Medalists). Retinopathy, nephropathy, neuropathy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
188
3
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(206 citation statements)
references
References 24 publications
10
188
3
5
Order By: Relevance
“…It has been suggested that circulating and endothelial progenitor cells are involved in protection from cardiovascular complications and nephropathy 23. It was also shown that certain advanced glycation endproducts were inversely associated with proliferative diabetic retinopathy in long‐term survivors, as opposed to previous studies that showed strong associations between advanced glycation endproducts and diabetes complications 18. Thus, long‐term survivors of diabetes appear to develop a compensatory mechanism against the hazardous effects of advanced glycation endproducts, but the exact dynamic has yet to be discovered 24.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that circulating and endothelial progenitor cells are involved in protection from cardiovascular complications and nephropathy 23. It was also shown that certain advanced glycation endproducts were inversely associated with proliferative diabetic retinopathy in long‐term survivors, as opposed to previous studies that showed strong associations between advanced glycation endproducts and diabetes complications 18. Thus, long‐term survivors of diabetes appear to develop a compensatory mechanism against the hazardous effects of advanced glycation endproducts, but the exact dynamic has yet to be discovered 24.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, we found a major confounding effect by obesity, but not HbA 1c , and we found no strong positive associations between plasma pentosidine and incident cardiovascular events. Besides their role in CVD, AGEs have been linked to development of microvascular complications of diabetes (1), but interestingly, some plasma AGEs have been linked to higher, while other have been linked to lower risk of microvascular complications (38). As the associations between plasma AGEs and microvascular complications in T2DM are largely unknown, this should be addressed in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of these patients have PDR, as might be expected given their long duration of diabetes. However, a substantial proportion (nearly 40%) of the patients, all of whom were diagnosed with diabetes decades before strict glycemic control was standard practice, surprisingly still have no or mild DR (111). In contrast to other large studies in groups with shorter-duration diabetes, DR severity has not been associated with current or longitudinal HbA1c values in this cohort, which suggests the presence of endogenous protective factors in those individuals who have not progressed to advanced diabetic complications, including retinopathy.…”
Section: Future Directionsmentioning
confidence: 99%